The right of self-determination and the use of the force in public international law - Zikamabahari, Jean de Dieu (School For Advanced Legal Studies, 2026)
Self-determination is a people's right to choose how they will organise and be governed. It is the legal foundation on which a people's struggle for national liberation is based. This dissertation examines how self-determination has developed from a political thought to a legal right in international law. It also assesses the legitimacy of the use of force by liberation movements to secure the right of peoples to self-determination. In international practice, self determination has been subject to a conceptual evolution which began in the nineteenth century and accelerated in the 1960's due to the decolonisation process. Today, the principle of self-determination is part of customary international law and it is indisputably a norm of jus cogens. While the concept has been liberally used as a slogan of universal application, its application always seems to be a rather complex matter with several obstacles. Article 2 (4) of the United Nations (UN) Charter laid down an absolute prohibition of the use of force except in case of self-defence or when the UN Security Council (SC) considers the use of force to be the ultimate resort. The Charter does not expressly mention self-determination as a situation where people may resort to the use of force for example against colonial, alien, or oppressive regimes. This dissertation looks at the history of, and circumstance surrounding, the use of force, and then examines the jusadhelium regarding 'wars' of liberation movements. Classical international law treats civil wars as purely internal matters. There was gap m international law in relation to the rule against rebellion. Article 2(4) of the Charter prohibits the threats or use of force by states against states. It is not so clear on the use of force by oppressed peoples in pursuit of self-determination. The idea that colonial or oppressed peoples may legitimately use force in pursuit of self-determination thus remains ambiguous. It is argued that if force was used to deprive peoples of their right to self-determination they would have the right to use force in self-defence. Apart from the Charter, the study analyses a number of resolutions regarding the right of self-determination. It finds that through state practice and opinion juris there is an emerging customary international law regulating the use of force in pursuit of self-determination.